Teacher Strategies in Instilling Disciplinary Character in Early Childhood - Lamadang, Karmila P.; Rahma; Salingkat, Sahrul; Hairi, Cici Aprianti (International Journal of Sustainability in Research, 2024)
Teacher strategy is how teachers instill discipline in children. This research uses a qualitative approach. The aim of this research is 1) to find out teachers' strategies for instilling disciplined character in the Joint Development Early Childhood Education in Lalong Village. 2) To find out the character of discipline in preschool children developed in Lalong Village. The methodology for writing this thesis uses a qualitative approach; data collection uses observation, interview, and documentation techniques. Teacher's Strategy for Instilling Disciplinary Character in Early Childhood Development Education with Lalong Village. The research results show that strategies that should be implemented are: 1) teacher examples. 2) maximize school regulations. 3) pursue moral and religious values. From the results of implementing several strategies above, positive results are quite satisfactory in the development of children's discipline, such as: a) increasing children's awareness of the existence of God; and b) children becoming more enthusiastic when teachers provide material about religion (reading and memorizing short prayers). b) Children increasingly appreciate time; they don't want to be late. c) Feel comfortable and happy when you are at PAUD Bina Bersama. d) Always appear neat, clean, and modest, and have awareness of personal and environmental cleanliness. e) Respect others and elders.